Empirical Analysis of Trilemma in Emerging Economies - Akinkunmi, Mustapha A (Asian Development Policy Review, 2017)
The increasing debate on empirical evidences in testing the Mundell-Fleming theory has been the focus of this study. The study examines the effect of central banks’ interventions on trilemma constraint using a panel dataset of 30 emerging market economies for the sample period 1980-2014. With the aid of the portfolio balance framework, the findings indicate that the weighted sum of the three trilemma objectives falls in the presence of foreign exchange market intervention. The capacity to loosen the constraints has decreased over time and has been most substantial in African emerging economies.